A Systematic Review Of Prevalence And Risk Factors Of Latent Tuberculosis Infection Among Medical And Nursing Students - Zarini Ismail; Siva Gowri a/p Pathmanathan; Lailatul Hazzliza Musa; Muslimah Ithnin; Nurul Azmawati Mohamed; Nizam Baharom; Shalinawati Ramli (Faculty of Medicine and Health Sciences, UPM, 2024)
Indexed by SCOPUS/MYCITE